Linking CGE and Microsimulation Models: A Comparison of Different Approaches - Giulia Colombo (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
In the paper we describe in detail how to build linked CGE-microsimulation models (using fictitious data) following three main approaches: one in accordance with the fully integrated approach and the other two according to the layered approach – the so-called Top-Down and Top-Down/Bottom-Up approaches. After this, we implement the same policy reform in each of the three models. Results show that all three approaches yield different results especially in terms of income distribution and poverty, although analysed within the same economy and under the same policy simulation. We then analyse in more detail the TD/BU approach as developed by Savard (2003) and, in order to avoid possible deviations due to data inconsistencies, we propose an alternative way of taking into account feedback effects from the micro level of analysis into the CGE model.
Keywords: C68; D31; C35; C15; 330; CGE models; microsimulation; income distribution; CGE-Modelling; Mikrosimulation; Wissenschaftliche Methode; Vergleich; Wirtschaftsreform; Simulation; Verteilungswirkung; Theorie